2016
DOI: 10.1111/apa.13444
|View full text |Cite|
|
Sign up to set email alerts
|

Using a high‐flow nasal cannula provided superior results to low‐flow oxygen delivery in moderate to severe bronchiolitis

Abstract: CORRIGENDUM Milani GP et al. (2016) Using a high-flow nasal cannula provided superior results to low-flow oxygen delivery in moderate to severe bronchiolitis. Acta Paediatr 105: e368-72. doi: 10.1111/apa.13444. In the article 'Using a high-flow nasal cannula provided superior results to low-flow oxygen delivery in moderate to severe bronchiolitis', the formula reported to calculate the nasal cannula flow is incorrect. The formula used to calculate the flow rate (L/minute) of the high-flow nasal cannula was 8 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 22 publications
2
67
0
12
Order By: Relevance
“…The pooled effect was so high in this review that HFNC therapy proved cost‐effective when it was compared to standard low‐flow oxygenation . In a prospective semi‐randomised pilot study , the median length of stay in hospital was three days shorter in 18 bronchiolitis patients treated with HFNC and the median duration of oxygen administration was two days shorter when they were compared to those treated with low‐flow oxygenation. Thus far, only two RCT studies have been published on HFNC for bronchiolitis .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The pooled effect was so high in this review that HFNC therapy proved cost‐effective when it was compared to standard low‐flow oxygenation . In a prospective semi‐randomised pilot study , the median length of stay in hospital was three days shorter in 18 bronchiolitis patients treated with HFNC and the median duration of oxygen administration was two days shorter when they were compared to those treated with low‐flow oxygenation. Thus far, only two RCT studies have been published on HFNC for bronchiolitis .…”
Section: Discussionmentioning
confidence: 86%
“…One study of 27 infants found that oxygen saturation increased within one hour of starting HFNC and respiratory rate decreased within three hours . In a semi‐randomised pilot study of 36 infants, the respiratory rate decreased during the first hour and was constant after that . Another study of 61 infants found that the heart rate and respiratory rate decreased rapidly in those that responded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome measures were respiratory rate, the doctors’ clinical assessment of respiratory effort and the ability to feed, which was assessed by nurses who recorded the infants’ milk intake during bottle‐feeding or weighed the infants before and after breastfeeding. The improvements in respiratory rate and effort, and the ability to feed, were significantly faster in the infants treated with HFNC than in the controls . The median duration of oxygen support was 4 days (interquartile, IQ 3–5 days) in the HFNC group versus 6 days (IQ 5–7 days) in the standard low‐flow oxygen group, and the median lengths of hospital stays were 6 days (IQ 5–7 days) versus 9 days (IQ 8–10 days), respectively.…”
mentioning
confidence: 93%
“…In this issue of the journal, Milani et al. report the results of their prospective observational study on the use of HFNC therapy in moderate‐to‐severe infant bronchiolitis treated on the paediatric ward, comparing their results with standard low‐flow oxygen administration. The study included 36 infants aged 1.2–5.0 months who needed oxygen support when they were treated on a paediatric ward.…”
mentioning
confidence: 99%